Phylogenetic Group/Subgroups Distributions, Virulence Factors, and Antimicrobial Susceptibility of Escherichia coli Strains from Urinary Tract Infections in Hatay - Ebru Şebnem Yılmaz; Özkan Aslantaş (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: Nosocomial and community acquired urinary tract infections (UTIs) are one of the most encountered infections in the world. METHODS: This study aimed to determine the antibiotic susceptibility, phylogeny, and virulence genes of 153 Escherichia coli strains isolated from UTIs. Antimicrobial susceptibility of the isolates to different classes of antimicrobials was determined by the VITEK-2 automated system. Presence of virulence genes and phylogenetic groups were investigated by PCR. RESULTS: Regarding susceptibility to antimicrobials, ampicillin resistance was most abundant (67.3%), followed by amoxicillin-clavulanic acid (50.9%); least abundant was resistance to amikacin (1.3%) and nitrofurantoin (1.3%). Multi drug resistance (MDR) was observed in 34.6% of the isolates, and all isolates were found to be susceptible to imipenem, meropenem and fosfomycine. The majority of the isolates belonged to the phylogenetic group B23 (35.9%), followed by A1 (20.9%), D1 (18.9%), D2 (12.4%), A0 (%5.9), B1 (3.9%) and B2 (1.9%). Among E. coli strains examined, 49% had iucD, 32.7% papE-F, 26.1% papC, 15% cnf2, 11.1% sfa, 7.8% cnf1, 1.3% afaE, 1.3% afaD, 1.3% hlyA, 0.7% f17a-A, 0.7% clpG and 0.7% eaeA genes. CONCLUSIONS Our research demonstrated that virulence factors were distributed among different phylogroup/subgroups, which play a role in UTIs pathogenesis in humans. For this reason, complex and detailed studies are required to determine the relationship between virulence factors and specific E. coli strains that cause UTIs in humans.